2021
DOI: 10.1002/jlb.3a0121-003rr
|View full text |Cite|
|
Sign up to set email alerts
|

B10 cells decrease fibrosis progression following cardiac injury partially by IL-10 production and regulating hyaluronan secretion

Abstract: B10 cells play negative roles in inflammatory disorders by producing IL‐10. However, their effects on fibrosis have not been elucidated. Therefore, this study was conducted to examine the dynamic changes of B10 cell frequency and their potential role in cardiac fibrosis. We found that the frequency of B10 cells was significantly increased, and they participated in the regression of fibrosis via IL‐10, particularly by accelerating hyaluronan secretion and inhibiting collagen deposition. In vivo, hyaluronan abla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Further studies have also shown that mesenchymal stem cells of non-hematopoietic origin can instead be mobilized to differentiate cardiomyocytes ( Kawada et al, 2004 ; Fukuda and Fujita, 2005 ), thus highlighting the potential significance of characterizing the CD45 − fetal microchimeric cells. This antibody panel does not also characterize different B cell subpopulations, as certain subsets such as B10 cells have been implicated in less fibrosis during cardiac repair ( Wu et al, 2019 ; Chen et al, 2022 ). Aside from the limitations intrinsic to the antibody panel used, another limitation was the sample size and duration of observation for the echocardiographic studies.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies have also shown that mesenchymal stem cells of non-hematopoietic origin can instead be mobilized to differentiate cardiomyocytes ( Kawada et al, 2004 ; Fukuda and Fujita, 2005 ), thus highlighting the potential significance of characterizing the CD45 − fetal microchimeric cells. This antibody panel does not also characterize different B cell subpopulations, as certain subsets such as B10 cells have been implicated in less fibrosis during cardiac repair ( Wu et al, 2019 ; Chen et al, 2022 ). Aside from the limitations intrinsic to the antibody panel used, another limitation was the sample size and duration of observation for the echocardiographic studies.…”
Section: Discussionmentioning
confidence: 99%